LINGUISTIC ANALYSIS OF THE TRADITION OF GRATEFUL AND CURSING NAMES OF TURKISH-KAZAKH SOCIETY - Salkynbay , A.; Anuarbekova , A. (EurasianUnionScientists, 2021)
This article reflects the place of the grateful and cursing words in the life of the Kazakh and Turkish people, their functions and features of their use. Information about the origin and appearance of these words is collected. Based on the works of scientists who studied the thanksgiving and cursing words, the order and place of use of each of them is clarified using specific examples. It was shown that the basis of these words is directly related to the culture of the people.